Multi Attribute Utility Theory (MAUT) Method of Decision on The Selection of the Head of Study Program Digital Business - Aldo, Dasril; Army, Widya Lelisa; Syafrinal, Ilwan (JISA(Jurnal Informatika dan Sains), 2022)
The head of the study program is the spearhead of success in a study program. So a head of a study program is required to have good leadership and management skills in order to be able to carry out his duties and functions correctly. The problem that arises is that the appointment of a head of a study program is often carried out not looking at some aspects or criteria, usually the appointment is subjective and based on how long he has been a lecturer in the study program. Even though the appointment of a study program head must be seen from many aspects and criteria, this is done because if you appoint a study program head who is not competent, it can result in not running well with the study program he leads. The criteria used in this research are Functional Position, Education, Working Period, Research, PKM Activities, Supporting Activities and Lecturer Achievement. To overcome this problem, a decision support system with the MAUT method is the right solution to use. The advantage of the MAUT method is that the calculation and decision-making process is faster because it can directly calculate the final evaluation value without the need to compare the importance weight values between criteria. This method will process the criteria values of each candidate so that the results will be more objective. In this study, the number of alternatives used was 6 data on the value of the prospective head of the study program. Based on the MAUT process, a decision was obtained that the chosen head of the digital business study program was a Candidate-01 lecturer with a value of 1.0.